TRANSFORMASI DIGITAL SEKOLAH MELALUI PEMANFAATAN APLIKASI SITOPIK DAN OASE DI SDN TUGUREJO 02 KOTA SEMARANG - Agustin, Tri Fena Susi; Rosalina Ginting; Muhtarom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation has become a strategic necessity for elementary schools in improving the quality of learning and school performance. This study aims to describe and analyze the utilization of the SITOPIK and OASE applications as part of digital transformation at SDN Tugurejo 02. The research employed a qualitative approach with a case study design. Data collection techniques included interviews, observations, and documentation studies. The findings indicate that the utilization of the SITOPIK and OASE applications supports learning effectiveness, enhances teacher performance, and strengthens school governance. Digital transformation at SDN Tugurejo 02 is supported by the leadership of the school principal, teacher readiness, and a collaborative school culture. This study recommends strengthening mentoring and the continuous development of teachers’ digital competencies.